Early cardiovascular events in women with a history of gestational diabetes mellitus. Issue 1 (December 2016) - Goueslard, Karine; Cottenet, Jonathan; Mariet, Anne-Sophie; Giroud, Maurice; Cottin, Yves; Petit, Jean-Michel; Quantin, Catherine
Abstract Background The effect of gestational diabetes mellitus (GDM) on cardiovascular diseases (CVD) is not assessed within the first 10 years postpartum, regardless of subsequent diabetes. The aim of this study was to determine the risk of CVD events related to GDM within 7 years of postpartum. Methods This nationwide population-based study of deliveries in 2007 and 2008 with a follow-up of 7 years was based on data from the French medico-administrative database. Two groups were formed: women with a history of GDM and women without GDM or previous diabetes. CVD included angina pectoris, myocardial infarction, stroke, heart bypass surgery, coronary angioplasty, carotid endarterectomy and fibrinolysis. Hypertensive disease was assessed separately. Determinants studied included age, obesity, subsequent diabetes mellitus and hypertensive diseases during pregnancy. Adjusted odds ratios for outcomes were calculated using multiple logistic regressions. Results The hospital database recorded 1, 518, 990 deliveries in 2007 and 2008. Among these, 62, 958 women had a history of GDM. After adjusting for age, DM, obesity and hypertensive disorders in pregnancy, GDM was significantly associated with a higher risk of CVD (adjusted Odds Ratio aOR = 1.25 [1.09–1.43]). Considering each variable in a separate model, GDM was associated with angina pectoris (aOR = 1.68 [1.29–2.20]), myocardial infarction (aOR = 1.92 [1.36–2.71]) and hypertension (aOR = 2.72 [2.58–2.88]) but not with stroke. Conclusions A history of GDM was identified as a risk factor of CVD, especially coronary vascular diseases, within the 7 years postpartum. A lifestyle changes from postpartum onwards can be recommended and supported.